Keabsahan Poligami: Perspektif Muhammad Abduh dan Mahmud Syaltut - Rofiq, Aunur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2001)
Polygamy nowadays becomes a hot topic which deserves great attention. From the history, it is known that it had been practiced. Several Rasuls, Ibrahim, Ya 'kub, Daud and Sulaiman had more than one wife. When Islam came to Arab peninsula, polygamy was still in practice. Islam, then, provides the rules and limits people to only have four wives. This research is aimed at analyzing Abduhâ€™s Â and Syaltutâ€™s concepts' of polygamy. Even though the two proposed two contrasts ideas, but, seen from its norms, the two made use of justice as the main base of applying polygamy. In this sense, only few minor technical things differentiate the two concepts.